Sosialisasi Deteksi Dini Hama Wereng Menggunakan Teknologi Informasi di Desa Cabean, Kecamatan Sawahan, Kabupaten Madiun - Utomo, Pradityo; Budiman, Arief (JURNAL DAYA-MAS, 2020)
Indonesia is one of the largest rice producing countries in the world. In rural areas, the majority of the population has a livelihood as rice farmers. Being a farmer also has several obstacles, one of which is the attack of planthopper on rice plants. This makes the yield less optimal. Farmers must be vigilant from the outset against planthopper pests. Onward with the development of technology, farmers can use information technology as a learning tool to detect planthopper pests early and control them. The result of the development of information technology that every community uses and owns is an Android-based smartphone. For this reason, with the socialization of the application of early detection of planthopper pests and their control using biological agents can help farmers in managing rice plants. The app is made based on Android, so farmers can install the application into a smartphone to detect planthopper pests. Whereas for the control of planthopper pests selected using Biological Agent, because Biological Agents are a safer way to control planthopper pests than using pesticides. By utilizing Android applications and biological agents, farmers are expected to get maximum yields.Keywordsâ€”: Rice; Wereng Pest; Socialization;Â  Biological Agents.